2019
DOI: 10.1590/s0034-759020190103
|View full text |Cite
|
Sign up to set email alerts
|

A Representação Social De Cloud Computing Pela Percepção Dos Profissionais Brasileiros De Tecnologia Da Informação

Abstract: RESUMO Este estudo busca identificar a representação social sobre Cloud Computing, pela percepção dos profissionais brasileiros de Tecnologia da Informação (TI). Os dados empíricos foram coletados por meio de questionários on-line respondidos por uma amostra por acessibilidade de 221 profissionais de TI e analisados por meio da Teoria da Representação Social (TRS), operacionalizada pelas técnicas de evocação livres de palavras e do quadro de quatro casas de Vergès, bem como pelas análises implicativa, léxica e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
0
15
0
3
Order By: Relevance
“…The average professional experience of the 140 respondents was 16.9 years and their average age was 44.1 years old. Marchisotti (2014), in research on the social representation of cloud computing according to IT professionals, found similar values, namely 15 years for the average professional experience and 40 years old for the average age of the respondents.…”
Section: Sample's Demographicsmentioning
confidence: 72%
“…The average professional experience of the 140 respondents was 16.9 years and their average age was 44.1 years old. Marchisotti (2014), in research on the social representation of cloud computing according to IT professionals, found similar values, namely 15 years for the average professional experience and 40 years old for the average age of the respondents.…”
Section: Sample's Demographicsmentioning
confidence: 72%
“…Os usuários pagam pelo serviço como despesa operacional, sem incorrer em despesas de capital inicial significativo, assim, as despesas com TI nas organizações convertem-se de despesas de capital CAPEX (Capital Expenditure) para despesas operacionais OPEX (Operational Expenditure). (MARCHISOTTI et al, 2019).…”
Section: Cloud Computingunclassified
“…For the elaboration of the Vergès' quadrant, it is necessary that two parameters are calculated: the average frequency of evocation (AFE) and the mean value of the average order of evocation (AOE) of the words [47]. These values are reference points for correctly disposing the evoked words within each quadrant, crossing, for each word, the frequency of evocation, of a quantitative nature, with the average order of evocation, of a qualitative nature [47,55,56].…”
Section: Close Link With the Central Nucleusmentioning
confidence: 99%